SOIL PROPERTIES OF THE ALLUVIAL PLAIN AND ITS POTENTIAL USE FOR AGRICULTURE IN DONGGALA REGION, CENTRAL SULAWESI - M. Al-Jabri (Indonesian Agency for Agricultural Research and Development, 2007)
Agricultural lands of Donggala region are extensively distributed in alluvial plain. However, information on soil properties and fertility constraints has not been known in detail. An investigation of soil resources was conducted in September 2003 and December 2004 to characterize surface soil properties of alluvial plain and to evaluate soil fertility constraints. For this study, 55 representative soil profiles consisting of 187 soil samples were selected for physical, chemical, and mineralogical analyses. The soil profiles were classified as soil groups of Ustifluvents, Haplustepts, Eutrudepts, and Endoaquepts. All the soil physical and chemical data were calculated as weighted average based on top 30 cm soil layer analyses. The results showed that soil texture ranged from sandy loam to loam. In ustic moisture regime, the average pH was neutral (7.0-7.2), but in udic moisture regime it was slightly acid (5.5-6.2). In all soil groups, the organic carbon content was very low to low (0.58-1.44%), P retention was very low (3-18%), and soil cation exchange capacity (CEC) was very low to low (9-14 cmol(+) kg-1). In contrast, all the soil groups showed very high content of potential phosphate (81- 118 mg P2O5 100 g-1) and potassium (338-475 mg K2O 100 g-1), but the available phosphate and potassium were 16-47 mg kg-1 P and 0.18-0.35 cmol(+) kg-1, respectively, which were considered to be low to medium range. The very high P2O5 and K2O were probably derived from weathered mica-schist and granite rocks, but low exchangeable K was probably due to K fixation. The sand mineral fraction was composed of relatively high (> 20%) weatherable minerals of acid parent materials, such as orthoclase and sanidine, while the clay mineral was composed of smectite and illite. The low soil-CEC, low organic matter, and exchangeable K contents were the main soil fertility constraints. Therefore, soil management should be directed to organic matter application to increase soil carbon content, CEC, and nutrient availability. Fertilizer recommendation for wetland rice and several upland crops is suggested based on the soil properties.